The book of Fred - Bardi, Abby (New York : Washington Square Press, 2001)
Raised in a fundamentalist sect, 15-year-old Mary Fred Anderson has never watched TV, been to a supermarket, or read anything beyond the inscrutable dogma of the prophet Fred. When her parents are jailed, Mary Fred is put into foster care in a Washington, D.C. suburb. As she struggles to understand the modern world, Mary Fred begins to positively influence her troubled housemates.
Includes a readers club guide with reading group questions and topics for discussion, as well as an interview with the author.
Keywords: Fundamentalism -- Fiction; Teenage girls -- Fiction; Humorous fiction